1979
DOI: 10.2134/agronj1979.00021962007100030021x
|View full text |Cite
|
Sign up to set email alerts
|

N Deprivation in Maize During Grain‐Filling. II. Remobilization of 15N and 35S and the Relationship between N and S Accumulation1

Abstract: The role of N and S remobilization in ear development of maize (Zea mays L.) has not been adequately assessed. The objective of this greenhouse experiment was to determine the effect of N deprivation during grain‐filling on N and S remobilization and the relationship between N and S accumulation. Maize plants were grown in nutrient solution containing 15N‐nitrate and 35S‐sulfate. After silking, the plants were placed in unlabelled solutions, with or without nitrate‐N. The amount of labelled and unlabelled N an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0
1

Year Published

1981
1981
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 8 publications
(9 reference statements)
0
17
0
1
Order By: Relevance
“…The changes in stalk carbohydrates and reduced nitrogen during stalk elongation show the stalk serves as a storage reservoir and these reserves are remobilized during the final stage of kernel development (1,3). However, translocation ofC and N have been often considered independently (11,13), even though metabolism of C and N are closely linked (3). Sucrose transfer from vegetative parts to the ear is linked to zein accumulation in maize kernels (21).…”
Section: Materials and Methods Plant Culture And Labeling Experimentsmentioning
confidence: 99%
“…The changes in stalk carbohydrates and reduced nitrogen during stalk elongation show the stalk serves as a storage reservoir and these reserves are remobilized during the final stage of kernel development (1,3). However, translocation ofC and N have been often considered independently (11,13), even though metabolism of C and N are closely linked (3). Sucrose transfer from vegetative parts to the ear is linked to zein accumulation in maize kernels (21).…”
Section: Materials and Methods Plant Culture And Labeling Experimentsmentioning
confidence: 99%
“…In maize, studies reported an early remobilization of N from the stem before the leaf lamina (Beauchamp et al. , Friedrich and Schrader ). Thus, high stem N remobilization efficiency would potentially favour high NUtE through delayed senescence of the leaf lamina.…”
Section: Traits Influencing N Utilization Efficiencymentioning
confidence: 99%
“…We will consider here only long-term labeling in the fi eld. In maize, long-term labeling has already been used for studying the distribution among organs of the N taken up at various developmental stages of the plant (Friedrich and Schrader, 1979;Below et al, 1985;Cliquet et al, 1990aCliquet et al, , 1990bDeléens et al, 1994;Ma and Dwyer, 1998). In other 15 N labeling studies, the proportion of remobilized N has been estimated by calculating the diff erence between the quantity of 15 N accumulated in the stover at silking and the quantity of 15 N accumulated in the stover at maturity (Mae and Ohira, 1981;Ta and Weiland, 1992).…”
mentioning
confidence: 99%